Rainfall asymmetries of the western North Pacific tropical cyclones as inferred from GPM. (5th May 2021) - Liang, Junyi; Chan, Kelvin T. F.
Abstract: It has been revealed that the vertical wind shear (VWS) can result in the rainfall asymmetry of tropical cyclone (TC), where the VWS is conventionally defined as the environmental horizontal winds between 200‐ and 850‐hPa levels within a certain area from the TC centre. The rainfall maximum is generally displaced downshear to downshear‐left side in the Northern Hemisphere or downshear to downshear‐right side in the Southern Hemisphere. Here, we revisit the rainfall asymmetries of TCs over the western North Pacific using the state‐of‐art Global Precipitation Measurement data. Observations pose that using the conventional VWS to interpret the TC rainfall asymmetry is inopportune. The conventional VWS can only largely grasp the rainfall asymmetry in the inner core of TC, but not in the outer core. We, therefore, explicitly propose a new VWS, namely the effective VWS, to fill this gap. The effective shear layer responsible for the rainfall asymmetry is a function of TC intensity and core region. In addition, we suggest that the angle difference between the effective shears for the inner‐core and outer‐core rainfall asymmetries can help to comprehend the spirality of the rainfall asymmetries that are, the fashions, or patterns of the rainbands. Meanwhile, the moisture flux convergence and storm motion show little effect on the rainfall asymmetry. This study advances the understanding of TC rainfall asymmetry and provides scientific support for disaster prediction, prevention, and mitigation. Abstract : Using the conventional vertical wind shear (VWS) to interpret the tropical cyclone (TC) rainfall asymmetry is inopportune. An effective VWS is proposed where it is a function of TC intensity and core region. The angle difference between the effective shears for the inner‐core and outer‐core rainfall asymmetries can help to comprehend the fashions of the rainfall asymmetries.